Renin inhibitors versus angiotensin converting enzyme (ACE) inhibitors for primary hypertension - Wang, Gan Mi (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the efficacy and safety of renin inhibitors compared to ACE inhibitors in people with primary hypertension.